Perancangan dan Penerapan ISO 9001:2008 di PT. Teno Tract Indonesia - Diah Parwati Dewi Bintoro; Jani Rahardjo (Jurnal Titra, 2015)
PT. Teno Tract Indonesia, a foundation piling company, had dealt with many type of building construction for private sector, and now wants to get government projects. However, the government requires that PT Teno Tract Indonesia has ISO certificate. Hence, PT. Teno Tract Indonesia planned and prepared to implement quality management system based on ISO 9001:2008. PT. Teno Tract Indonesia also want to increase customer satisfication and improve management system. Three stages to get ISO 9001: 2008 certificate are planning stage, implementation stage and also scoring stage. Planning stage consists of mapping, identification, and documentation. The second stage is quality management system implementation. The last stage is scoring via internal audit. Audit has to be done to know compability of system that has been run based on standard requirements of ISO 9001 : 2008. Based on internal audit simulation, PT Teno Tract Indonesia has been ready to submit the papers to get ISO certification.